The role of emergent champions in policy implementation for decentralised drug-resistant tuberculosis care in South Africa. Issue 12 (9th December 2022) - Le Roux, Sacha Roxanne; Jassat, Waasila; Dickson, Lindy; Mitrani, Leila; Cox, Helen; Mlisana, Koleka; Black, John; Loveday, Marian; Grant, Alison D; Moshabela, Mosa; Kielmann, Karina; Nicol, Mark P
Abstract : Objective: Champions are recognised as important to driving organisational change in healthcare quality improvement initiatives in high-income settings. In low-income and middle-income countries with a high disease burden and constrained human resources, their role is highly relevant yet understudied. Within a broader study on policy implementation for decentralised drug-resistant tuberculosis care in South Africa, we characterised the role, strategies and organisational context of emergent policy champions. Design: Interviews with 34 healthcare workers in three South African provinces identified the presence of individuals who had a strong influence on driving policy implementation forward. Additional interviews were conducted with 13 participants who were either identified as champions in phase II or were healthcare workers in facilities in which the champions operated. Thematic analyses using a socio-ecological framework further explored their strategies and the factors enabling or obstructing their agency. Results: All champions occupied senior managerial posts and were accorded legitimacy and authority by their communities. 'Disease-centred' champions had a high level of clinical expertise and placed emphasis on clinical governance and clinical outcomes, while 'patient-centred' champions promoted pathways of care that would optimise patients' recovery while minimising disruption in other spheres of their lives. Both types of champions displayed high levels of resourcefulness and flexibility to adapt strategies to the resource-constrained organisational context. Conclusion: Policymakers can learn from champions' experiences regarding barriers and enablers to implementation to adapt policy. Research is needed to understand what factors can promote the sustainability of champion-led policy implementation, and to explore best management practices to support their initiatives.